2020
DOI: 10.1088/1742-6596/1660/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study and Antibiotic susceptibility patterns of some Extended Spectrum Beta-Lactamase Genes (ESBL) of Klebsiella pneumpniae in Urinary Tract Infections

Abstract: The present study included the collection of 121 samples from MSU for investigating the presence of K.pneumoniae in UTIs, the samples have been collected from Al-Shaheed Mohammed Baqir AL-Hakeem hospital and private laboratories in Baghdad province. The study was carried out through March 2019 to the beginning of June 2019. The samples were identified based on the morphological and microscopically characteristics of the colonies when they were culturing on number of culture media as well as biochemical tests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Another study from Erbil (Tawgozy and Amin, 2018), Duhok (Naqid et al, 2020), Baghdad (Al-Hashimy and Al-Musawy, 2020), Russia (Khaertynov et al, 2018), andIran (Kashefieh et al, 2021) found comparable results. While imipenem and meropenem, followed by amikacin and Ciprofloxacin, have demonstrated good activity and effectiveness against K. pneumoniae, this finding is consistent with a study conducted in Erbil by (Ali and Ismael, 2017). Furthermore, another review from China (Effah et al, 2020) observed a similar issue.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another study from Erbil (Tawgozy and Amin, 2018), Duhok (Naqid et al, 2020), Baghdad (Al-Hashimy and Al-Musawy, 2020), Russia (Khaertynov et al, 2018), andIran (Kashefieh et al, 2021) found comparable results. While imipenem and meropenem, followed by amikacin and Ciprofloxacin, have demonstrated good activity and effectiveness against K. pneumoniae, this finding is consistent with a study conducted in Erbil by (Ali and Ismael, 2017). Furthermore, another review from China (Effah et al, 2020) observed a similar issue.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, a study by (Alcántar-Curiel et al, 2018) suggested that while it appears that antibiotic resistance and the bacterial ability to form biofilm play a significant role in the worldwide spread of K. pneumoniae, the unambiguous relationship between these elements has not been fully recognized and expanded.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of bla TEM , bla CTX-M , and bla SHV was done by multiplex PCR (M-PCR) using specific primers (Promega Corp, Germany) as previously published (Table 1) 21,22 . Each PCR reaction included a 20 μL volume, comprising 10 μL of ×1 PCR buffer (pH 8.3), 1.5 nm of MgCl 2 , 200 nM each of the deoxynucleotide triphosphates, 0.5 μL of 40 pmol each of the forward and reverse primers, 1 μL of genomic DNA template (~100 ng), 1.25 U of Taq polymerase (Promega Corp, Germany), and DNA/RNA free water up to 20 μL.…”
Section: Detection Of Extended-spectrum β-Lactamases Genesmentioning
confidence: 99%